Active job-search programs a promising tool? A microeconometric evaluation for Austria - Andrea Weber; Helmut Hofer (Institute for Advanced Studies (IHS), 2003)
In Austria active job-search programs were introduced on a large scale in 1999. These programs aim at activating unemployed at an early stage and bringing them back to work by training job-search related skills. We evaluate the impact of active labour market programs in Austria on individual unemployment durations, and allow program effects to vary between active job-search programs and formal training programs. We use the timing-of-events method which estimates the program effect as a shift in the transition rate from unemployment to jobs at the moment of program entry. We find that participation in active job-search programs significantly reduces unemployment durations, whereas formal training programs have a negative effect on unemployment durations. For women all programs have positive effects.
Keywords: C14; C41; J64; J68; 330; active labour market policy; treatment effect; multivariate duration model; Arbeitsplatzsuchmodell; Arbeitsmarktpolitik; Multivariate Analyse; Österreich